Dressed Bodies, Neat Appearances and Cursed Luxury: Towards a Body Aesthetic in the Colombian School (2017)
This article discusses how the students’ bodies, especially the poor children’s bodies, became a bone of contention, a site of fights for their control and production, where civilizing speeches operated and they were manifested through dress code policies, uniform dress code policies and a broad range of aestheticizing technologies. In this regard, the article begins with the presentation of the general framework of the archeo-genealogical research on student uniforms and dress code in the Colombian school between the end of the 19th and beginning of the 20th centuries in which this text is inscribed. Then, a reference is made about the modern aesthetic project that made school an aestheticizing machine. Lastly, the relation between student uniform, hygiene, and good manners cultivation is presented. Thus, this text starts from the comprehension of student uniforms as aesthetic technologies integrating a wide range of knowledge, methods, practices and tools aimed at constructing the children’s bodies based on a truly particular regime.